Phytase Supplementation Effects on Amino Acid Digestibility in Broiler Chickens are Influenced by Dietary Calcium Concentrations but not by Acid-Binding Capacity. Issue 8 (24th July 2021) - Siegert, Wolfgang; Krieg, Jochen; Sommerfeld, Vera; Borda-Molina, Daniel; Feuerstein, Dieter; Camarinha-Silva, Amélia; Rodehutscord, Markus
ABSTRACT: Background: Responses to dietary calcium (Ca) and supplemented phytase on prececal amino acid digestibility (pcAAD) in broiler chickens vary among studies. The variation may arise from the dietary acid-binding capacity (ABC) that influences the activity of enzymes in the digestive tract and from microbial activity. Objective: This study aimed to investigate whether the ABC influences phytase effects on pcAAD and whether microbial activity contributes to this. Methods: Male Ross 308 broiler chickens were provided 1 of 12 diets in 72 pens (15/pen) from day 16 of age until the end of the experiment on days 21 or 22. In a 3 × 2 × 2-factorial arrangement, the ABC was varied by replacing calcium carbonate (CaCO3 ) with Ca-formate or by adding formic acid to CaCO3 -containing diets, and contained 5.6 or 8.2 g Ca/kg and 0 or 1500 phytase units/kg. The ileum content was collected for pcAAD measurement and microbial community composition was used to investigate whether changes in pcAAD are related to the microbiota. Results: Three-factor ANOVA showed that reducing the ABC increased pcAAD (average 1.1 percentage points) and no significant interaction of the ABC with Ca concentration and phytase supplementation including 3-way interactions. Without phytase, increasing dietary Ca concentration decreased pcAAD (average 3.1 percentage points). Phytase supplementation increased pcAAD (average 2.1 and 5.0 percentage points at low and high Ca concentrations, respectively), to reach the same level for both Ca concentrations. Microbial functional predictions pointed towards an influence of the microbiota in the crop and ileum content on amino acid concentrations, as indicated by different relative abundances of predicted genes related to amino acid biosynthesis, degradation, and metabolism. Conclusions: Dietary Ca concentrations but not the ABC modulates the effect of supplemented phytase on pcAAD in broiler chickens. The microbiota might contribute to differences in pcAAD by changing the amino acid composition of the digesta. The extent of this effect is still unknown. Abstract : The dietary calcium concentration influenced the response of amino acid digestibility to phytase supplementation. The ABC increased amino acid digestibility but did not interact with Ca and phytase supplementation.